There is no health without Cultural Safety: why Cultural Safety matters. Issue 1 (2nd January 2022) - McGough, S.; Wynaden, D.; Gower, S.; Duggan, R.; Wilson, R.
Abstract : Background: Nurses and midwives predominately work in western-centric health care settings, which may not align with Indigenous perspectives of health and wellbeing. Nurses and midwives will also view care through their own cultural lens. Culturally inappropriate health care can reduce access and engagement in services and contribute to reduced health outcomes for Indigenous peoples. Australian codes of conduct for nurses and midwives now advocate for care that is holistic, free of bias and racism, challenges beliefs based on assumption, and is culturally safe for Indigenous peoples. However, there are varying understandings of cultural care, what it looks like, and how to best achieve it. Aim: To highlight the importance of cultural safety in health care and discuss the integration into nursing and midwifery practice. Design: Discussion paper. Discussion: Cultural safety has emerged in Australia as the framework to improve the access and quality of health care for Indigenous people and to improve disparities in health care outcomes. However, the application of these principles for nurses and midwives has not been widely explored. Misconceptions around the concept remain despite the inclusion in national standards and practice frameworks. Conclusion: Evaluation and research that contributes to evidence-based knowledge specifically on the integration of cultural safety in nursing and midwifery practice is required. Impact Statement: This paper provides an overview of the importance of cultural safety in nursing and midwifery practice. Although cultural safety is now embedded in professional codes and standards, there is limited evidence of how this is translated to clinical care. Research and evaluation are needed to evaluate the application of cultural safety principles by nurses and midwives.